UNDERSTANDING THE TRANSFORMATION PROCESS OF TAIPA WEAVING IN SOROWAKO, SOUTH SULAWESI: FROM TRADITIONAL HERITAGE TO CONTEMPORARY CULTURAL EXPRESSION - Chaerul Adam; Ira Wirasari; Riky Azharyandi Siswanto (Adisam Publisher, 2026)
Taipa Weaving is a cultural heritage of the Sorowako community, East Luwu Regency, South Sulawesi, which embodies historical, social, and cultural values through its distinctive motifs. However, the complexity of traditional motifs often limits public understanding and recognition of the cultural meanings they represent. This study aims to examine the transformation of Taipa Weaving motifs as an effort to enhance public understanding and recognition of the cultural values embedded within them. A qualitative descriptive approach was employed through observation, documentation, and interviews with local weavers and cultural practitioners. The findings reveal that Taipa Weaving motifs are derived from various local cultural artifacts, including pottery ornaments, stone engravings, traditional tools, and natural elements. These visual sources have undergone processes of simplification, stylization, and repetition, resulting in motifs that are more structured, recognizable, and suitable for textile applications while preserving their original cultural meanings. The transformation process reflects a form of cultural adaptation that enables local cultural values to remain relevant and accessible to contemporary society. The study concludes that motif transformation contributes to strengthening public recognition of Taipa Weaving and supports the preservation of Sorowako's cultural identity through more communicative visual representations.